Prognostic value of CT integrated with clinical and laboratory data during the first peak of the COVID-19 pandemic in Northern Italy: A nomogram to predict unfavorable outcome. Issue 137 (April 2021) - Angeli, Enzo; Dalto, Serena; Marchese, Stefano; Setti, Lucia; Bonacina, Manuela; Galli, Francesca; Rulli, Eliana; Torri, Valter; Monti, Cinzia; Meroni, Roberta; Beretta, Giordano Domenico; Castoldi, Massimo; et al.
Highlights: Visual analysis of chest CT allows a reliable quantitative evaluation of the extension of lung involvement (PI score) and consolidation (PC score). CT PI score allows prediction of ICU admission or death with an AUC of 0.722. Integration of clinical and laboratory data increases the CT prognostic value (ROC AUC 0.841). Abstract: Purpose: To evaluate the prognostic role of chest computed tomography (CT), alone or in combination with clinical and laboratory parameters, in COVID-19 patients during the first peak of the pandemic. Methods: A retrospective single-center study of 301 COVID-19 patients referred to our Emergency Department (ED) from February 25 to March 29, 2020. At presentation, patients underwent chest CT and clinical and laboratory examinations. Outcomes included discharge from the ED after improvement/recovery (positive outcome), or admission to the intensive care unit or death (poor prognosis). A visual quantitative analysis was formed using two scores: the Pulmonary Involvement (PI) score based on the extension of lung involvement, and the Pulmonary Consolidation (PC) score based on lung consolidation. The prognostic value of CT alone or integrated with other parameters was studied by logistic regression and ROC analysis. Results: The impact of the CT PI score [≥15 vs. ≤ 6] on predicting poor prognosis (OR 5.71 95 % CI 1.93−16.92, P = 0.002) was demonstrated; no significant association was found for the PC score. Chest CT had a prognostic role considering the PI score alone (AUC 0.722) and when evaluated with demographic characteristics, comorbidities, and laboratory data (AUC 0.841). We, therefore, developed a nomogram as an easy tool for immediate clinical application. Conclusions: Visual analysis of CT gives useful information to physicians for prognostic evaluations, even in conditions of COVID-19 emergency. The predictive value is increased by evaluating CT in combination with clinical and laboratory data.